2008
DOI: 10.1093/brain/awn030
|View full text |Cite
|
Sign up to set email alerts
|

Regional hippocampal atrophy in multiple sclerosis

Abstract: Gray matter brain structures, including deep nuclei and the cerebral cortex, are affected significantly and early in the course of multiple sclerosis and these changes may not be directly related to demyelinating white matter lesions. The hippocampus is an archicortical structure that is critical for memory functions and is especially sensitive to multiple insults including inflammation. We used high-resolution MR imaging at 3.0 T to measure hippocampal volumes in relapsing remitting MS (RRMS) and secondary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
295
6
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(345 citation statements)
references
References 42 publications
30
295
6
14
Order By: Relevance
“…Cognitive impairment is a common feature in MS and disturbances are mainly observed in anterograde memory (verbal and visual modalities), information processing speed, attention, working memory, vi-suospatial abilities and executive functioning (Chiaravalloti and DeLuca 2008). From a neurological standpoint, several neuroimaging studies carried out in MS patients have demonstrated that structures such as the frontal cortex (Benedict et al 2002;Bendfeldt et al 2009) and the hippocampus (Sicotte et al 2008;Hulst et al 2012), which are essential in the AM and EFT core network, are frequently damaged.…”
mentioning
confidence: 99%
“…Cognitive impairment is a common feature in MS and disturbances are mainly observed in anterograde memory (verbal and visual modalities), information processing speed, attention, working memory, vi-suospatial abilities and executive functioning (Chiaravalloti and DeLuca 2008). From a neurological standpoint, several neuroimaging studies carried out in MS patients have demonstrated that structures such as the frontal cortex (Benedict et al 2002;Bendfeldt et al 2009) and the hippocampus (Sicotte et al 2008;Hulst et al 2012), which are essential in the AM and EFT core network, are frequently damaged.…”
mentioning
confidence: 99%
“…Thalamic atrophy has been linked with fatigue and cognitive impairment [89,90], but the effect of DMAs on thalamic volume or function has not been assessed. The hippocampus is an archicortical gray matter structure that is impacted by MS and related to cognitive impairment [91]. Pathological studies show demyelination and neuronal loss throughout the hippocampal formation [92,93].…”
Section: Fig 1 Serial Cerebral Magnetic Resonance (Mr) Images Demonmentioning
confidence: 99%
“…16 A recent study showed a correlation between volume loss in the CA1 region of the hippocampus and reduced performance on a verbal-learning task in a group of RRMS patients. 17 Across different disease courses, people with MS often show reduced or impaired performance relative to age-matched controls. 2 Individuals with a progressive course typically do not perform as well as those with a relapsing-remitting course, but less consistent findings regarding cognitive abilities have emerged in comparisons of those with secondary progressive MS (SPMS) versus primary progressive MS (PPMS).…”
Section: Cognitive Domains Commonly Affected In Msmentioning
confidence: 99%